2011
DOI: 10.1111/j.1751-7893.2010.00249.x
|View full text |Cite
|
Sign up to set email alerts
|

Insight dimensions in first-episode psychosis patients: clinical, cognitive, pre-morbid and socio-demographic correlates

Abstract: When independently analysed, the three insight dimensions showed different rates of affectation and different predictors. These results suggest that there must be different mechanisms underlying the lack of insight. First-episode psychosis is a crucial period for treatment adherence formation, an issue strongly associated with good insight. Thus, a more accurate evaluation of the predictors of lack of insight into each dimension is warranted to achieve a better comprehension of the lack of insight in schizophr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 59 publications
(95 reference statements)
0
11
1
Order By: Relevance
“…Volume‐based analyses using a region of interest approach support the neuroanatomical model of impaired insight by reporting reduced right hemisphere volume in the right frontal lobe, including the orbitofrontal cortex, dorsolateral prefrontal cortex (DLPFC), anterior cingulate cortices (Flashman et al ., ; Shad et al ., , ), and the right parietal lobe (Shad et al ., ). However, voxel‐based morphometry studies using a whole brain approach have produced mixed results (Ha et al ., ; Bassitt et al ., ; Cooke et al ., ; Morgan et al ., ; Berge et al ., ). A more recent study, exploring hemisphere asymmetry, found relatively less right hemisphere volume in the DLPFC, and parietal and anteroinferior temporal lobe in relation to impaired insight (Gerretsen et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Volume‐based analyses using a region of interest approach support the neuroanatomical model of impaired insight by reporting reduced right hemisphere volume in the right frontal lobe, including the orbitofrontal cortex, dorsolateral prefrontal cortex (DLPFC), anterior cingulate cortices (Flashman et al ., ; Shad et al ., , ), and the right parietal lobe (Shad et al ., ). However, voxel‐based morphometry studies using a whole brain approach have produced mixed results (Ha et al ., ; Bassitt et al ., ; Cooke et al ., ; Morgan et al ., ; Berge et al ., ). A more recent study, exploring hemisphere asymmetry, found relatively less right hemisphere volume in the DLPFC, and parietal and anteroinferior temporal lobe in relation to impaired insight (Gerretsen et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Insight into illness is also an important predictor of relapse and outcome in first‐episode psychosis (FEP) . Several factors are associated with insight, and here transcultural aspects may be important . Cultural tradition and values influence our understanding of psychotic symptoms, and these may differ for immigrants compared with the reference population in their new country of residence.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 To our knowledge, only a few studies have addressed potential predictors of insight in first-episode psychosis (FEP) to date. Thus, neurocognition, 13,[17][18][19] premorbid personality, 11,14,17,20 premorbid adjustment, 18,19,21,22 education level 12 and duration of untreated psychosis (DUP) 14,18,23 have been found to affect insight in FEP. Mixed results have been found regarding correlates of insight -that is, associations with psychopathological symptoms.…”
Section: Introductionmentioning
confidence: 99%